2004
DOI: 10.1089/0894268041457138
|View full text |Cite
|
Sign up to set email alerts
|

IL-8 Inhibits Isoproterenol-Stimulated Ciliary Beat Frequency in Bovine Bronchial Epithelial Cells

Abstract: Mucociliary clearance is a critical host defense that protects the lung. The mechanisms by which mucociliary function is altered by inflammation are poorly defined. Chronic exposure to cigarette smoke decreases ciliary beating and interferes with proper airway clearance. Bronchoalveolar lavage (BAL) fluid from smokers and ex-smokers has increased amounts of IL-8, which has played a critical role in airway inflammation. We hypothesized that IL-8 might interfere with stimulated ciliary beating in airway epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…This observation supports our in vitro cellular studies of intact ciliated epithelial CBF desensitization to isoproterenol after chronic ethanol exposure (Wyatt and Sisson, 2001). Results from similar in vitro studies have shown that the ethanol desensitization response is not exclusively regulated at the level of the β-adrenergic receptors (Wyatt and Sisson, 2001), phosphodiesterase activation (Forgèt et al, 2003), or proinflammatory cytokine production (Allen-Gipson et al, 2004). Instead, ethanol appears to acutely stimulate CBF via nitric oxide (Sisson, 1995) and cAMP-dependent (Sisson et al, 1999) pathways.…”
Section: Discussionsupporting
confidence: 81%
“…This observation supports our in vitro cellular studies of intact ciliated epithelial CBF desensitization to isoproterenol after chronic ethanol exposure (Wyatt and Sisson, 2001). Results from similar in vitro studies have shown that the ethanol desensitization response is not exclusively regulated at the level of the β-adrenergic receptors (Wyatt and Sisson, 2001), phosphodiesterase activation (Forgèt et al, 2003), or proinflammatory cytokine production (Allen-Gipson et al, 2004). Instead, ethanol appears to acutely stimulate CBF via nitric oxide (Sisson, 1995) and cAMP-dependent (Sisson et al, 1999) pathways.…”
Section: Discussionsupporting
confidence: 81%
“…Employing a culture system of ciliated epithelial cells of rabbit trachea, it was shown that beta adrenergic stimulation increases ciliary beat frequency and this effect can be reversed by using a beta adrenergic receptor blocker, propranolol [30]. This adrenergic stimulatory effect is probably subject to modulation by other factors as exemplified by the ability of IL-8 to block the stimulatory effects of isoproterenol in a bovine model [31]. Based on a murine knockout model in which muscarinic receptors are deficient, it appears that cholinergic system does not have any effect on CBF in the oviduct [32].…”
Section: Adrenergic and Cholinergic Stimulationmentioning
confidence: 99%
“…Some rings were pretreated with an adenosine deaminase inhibitor, EHNA (10 M) or with a selective A 2B adenosine receptor antagonist, PSB1115 (100 nM), or with a selective and potent cAMP-dependent PKA inhibitor, KT-5720. Rings were incubated for 30 min at 37°C in 5% CO 2 and then allowed to equilibrate at 25°C for 10 min, and a final CBF reading was taken.…”
Section: Methodsmentioning
confidence: 99%
“…The cAMP-dependent PKA is established as an important regulator of the cilia stimulation pathway (2,42,51,62). To determine the mechanism of NECA-stimulation of CBF, we measured PKA activity in our primary ciliated BBEC model.…”
Section: L174 Adenosine Receptor Activation In Epithelial Ciliary Motmentioning
confidence: 99%
See 1 more Smart Citation